Nurse-like cells control the activity of chronic lymphocytic leukemia b cells via galectin-1 - Croci Russo, Diego Omar (2012)
Accumulation of neoplastic cells in chronic lymphocytic leukemia (CLL) is conditioned by a variety of signals delivered by accompanying cells in lymphoid tissues. Here we examined the relevance of galectin-1 (Gal-1), a glycan-binding protein with immunoregulatory activity, within the CLL microenvironment. We found that monocytes in peripheral blood and stromal and myeloid cells in bone marrow biopsies are the main source of Gal1. Knocking down Gal1 in adherent nurse-like cells differentiated in vitro decreased the expression of activation markers (CD80, CD86, CD25) and mRNA levels of IL10 and CCL3 in CLL cells. The concentration of Gal1 in plasma was increased in CLL patients compared to healthy subjects. Likewise, we found a higher expression of Gal1 in bone marrow biopsies from patients with progressive disease. These results provide the first evidence of a role for Gal-1 in CLL cell differentiation and its expression in accompanying myeloid cells.